2023
DOI: 10.1002/ecy.4060
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and stoichiometry dynamics of decomposing litter in stream ecosystems: A global synthesis

Abstract: Decomposing organic matter forms a substantial resource base, fueling the biogeochemical function and secondary production of most aquatic ecosystems. However, detrital N (nitrogen) and P (phosphorus) dynamics remain relatively unexplored in aquatic ecosystems relative to terrestrial ecosystems, despite fundamentally linking microbial processes to ecosystem function across broad spatial scales. We synthesized 217 published time series of detrital carbon (C), N, P, and their stoichiometric ratios (C:N, C:P, N:P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Notwithstanding, this effect of movement sequence on mass loss only occurred in coarse mesh bags. A short (i.e., 2 weeks) pre-conditioning terrestrial period followed by stream exposure contributed to a higher fungal biomass; although this is usually determinant of high leaf consumers' activity (Canhoto and Graça 2008), in our case it was likely not enough to surpass or compensate oak's inherent low leaf quality (e.g., thick cuticle, high lignin content, and leaf toughness) (Gulis et al 2006;Jabiol and Chauvet 2012;Robbins et al 2023), resulting in lower detritivore consumption. Likely, the potentially delayed leaching and microbial conditioning that occurred during the terrestrial pre-conditioning period may have delayed and restricted the optimal time window for aquatic detritivore activity.…”
Section: Discussionmentioning
confidence: 66%
“…Notwithstanding, this effect of movement sequence on mass loss only occurred in coarse mesh bags. A short (i.e., 2 weeks) pre-conditioning terrestrial period followed by stream exposure contributed to a higher fungal biomass; although this is usually determinant of high leaf consumers' activity (Canhoto and Graça 2008), in our case it was likely not enough to surpass or compensate oak's inherent low leaf quality (e.g., thick cuticle, high lignin content, and leaf toughness) (Gulis et al 2006;Jabiol and Chauvet 2012;Robbins et al 2023), resulting in lower detritivore consumption. Likely, the potentially delayed leaching and microbial conditioning that occurred during the terrestrial pre-conditioning period may have delayed and restricted the optimal time window for aquatic detritivore activity.…”
Section: Discussionmentioning
confidence: 66%
“…As leaf decomposition changes with time, the decomposition state of leaves controls their impact on the uptake of externally supplied nutrient (Cheever et al, 2012;Ferreira et al, 2015;Robbins et al, 2023;Webster et al, 2009). showing a shift from net nutrient uptake at an early state of leaf decomposition to net release at a later stage.…”
Section: Effects Of Leaf Additions On the Nutrient Uptake By Dark-gro...mentioning
confidence: 99%
“…Oviedo-Vargas et al (2013), for example, found no stimulation of P uptake through acetate additions in streams, probably due to autotrophic competition for the P and/or the microbial use of P and OC already stored in the sediments. Besides, P adsorption may dominate P retention in streams (Griffiths & Johnson, 2018;Robbins et al, 2023;Stutter, Graeber, & Weigelhofer, 2020) but this process is mostly independent of the OC availability (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations